2016
DOI: 10.1002/aqc.2712
|View full text |Cite
|
Sign up to set email alerts
|

Fish conservation in freshwater and marine realms: status, threats and management

Abstract: 1. Despite the disparities in size and volume of marine and freshwater realms, a strikingly similar number of species is found in eachwith 15 150 Actinopterygian fishes in fresh water and 14 740 in the marine realm. Their ecological and societal values are widely recognized yet many marine and freshwater fishes increasingly risk local, regional or global extinction.2. The prevailing threats in aquatic systems are habitat loss and degradation, invasive species, pollution, over-exploitation and climate change. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
282
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(309 citation statements)
references
References 147 publications
2
282
0
5
Order By: Relevance
“…Tanichthys albonubes has not been considered an endangered species by IUCN because aquarium specimens are easily kept and bred in a wide variety of water conditions. However, this freshwater fish cannot maintain self‐supporting populations in the wild as a result of many threats, including habitat loss, invasive species, water pollution, overfishing and climate change (Arthington, Dulvy, Gladstone, & Winfield, ). For example, Lee () proposed a mass release of captive‐bred stocks into various wetlands, but the present study found that these reintroduced populations could not exist in a stable state in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Tanichthys albonubes has not been considered an endangered species by IUCN because aquarium specimens are easily kept and bred in a wide variety of water conditions. However, this freshwater fish cannot maintain self‐supporting populations in the wild as a result of many threats, including habitat loss, invasive species, water pollution, overfishing and climate change (Arthington, Dulvy, Gladstone, & Winfield, ). For example, Lee () proposed a mass release of captive‐bred stocks into various wetlands, but the present study found that these reintroduced populations could not exist in a stable state in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical freshwater ecosystems support high biodiversity and important ecosystem services (Davidson, ; Tockner & Stanford, ). Tropical fishes in particular are highly vulnerable to habitat degradation, with this group comprising over 31% of freshwater species listed as at risk of extinction by the IUCN (Arthington, Dulvy, Gladstone, & Winfield, ; Darwall & Freyhof, ). A few studies have documented effects of land cover change on the taxonomic structure of fish communities in tropical streams (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…; Arthington et al. ). Based on knowledge of the Mountain Galaxias’ response to PIT tagging, this species may be used as a surrogate for other morphologically similar species, especially those in the Mountain Galaxias species complex.…”
Section: Discussionmentioning
confidence: 99%